the STRATEGI PENGEMBANGAN DESA DIGITAL UNTUK MENINGKATKAN LITERASI, PELAYANAN PUBLIK, DAN KEMANDIRIAN MASYARAKAT DI JAWA BARAT - Kusumawati, Riny (Universitas Djuanda, 2024)
Digital Village is a program that empowers communities to utilize digital technology and the internet to unlock the potentials of rural areas, market products, and increase access to information services. By increasing their digital literacy, individuals can use internet access to improve their quality of life, including environmental management, economics, education, management of the educational environment, innovation opportunities, and social stability. The emergence of the Industrial Revolution 4.0 and the challenges posed by the COVID-19 pandemic have caused significant changes in human behavior and habits. This transition is mainly influenced by advances in information technology and communications and the implementation of policies such as social distancing to mitigate the spread of COVID-19 information. Given these infrastructure needs, digitalization in rural areas presents a formidable challenge. This research aims to provide an in-depth overview of the public service process and application concepts that support making it easier for village officials to carry out administrative tasks that can be accessed via smartphone. It used qualitative descriptive research methods, followed by IBM SPSS reliability testing. This research data was collected through observation, interviews, and documents. The research results show that the Digital Village initiative uses technological information to improve the management of craft village businesses, market discovery, and identify business opportunities. In addition, Digital Village collaborates with various stakeholders at five levels to improve regional development programs. In the long term, the Digital Village program plays an essential role in increasing digital literacy, encouraging self-reliance, and improving the welfare of community in West Java.